Effect of gibberellin to honeydew severity and agronomical characters of soybean genotypes attacked by Bemisia tabaci - Dyah Kusuma Wardhani Syakhbikhisma Arsy; Siti Zubaidah; Heru Kuswantoro (The East Java Biological Society, 2017)
One of the factors that reduces soybean production is pest attack such as Bemisia tabaci. To increase soybean production, the physiological processes of the plant have to grow well causing optimal plant growth. It can be optimized by adding gibberellin. The research aimed to study the influence of gibberellin concentrations to honeydew severity and agronomical characters of soybean genotypes attacked by Bemisia tabaci. The gibberellin was given when the soybean plant was 35 days after planting. The gibberellin concentrations were 0, 25, 50, and 75 ppm. The result showed that the difference gibberellin concentrations did not affect honeydew severity, but the genotypes affected honeydew severity. The most susceptible genotype was shown by Gumitir. In the agronomical characters, UM 4-1 had the highest number of filled pods, but it was not significantly different from the variety of Wilis and UM 2-4. It was closely related to the number of total pods in which UM 4-1 also became the genotype producing the greatest number of total pods, although the yield was not quite different from the variety of Wilis and UM 2-4. Genotype of UM 4-1 also showed the highest number of total reproductive nodes per plant. The seed thickness was also influenced by genotype × gibberellins interaction. UM 2-4 at 50 ppm resulted the thickest seed. The 50 ppm concentration can provide an impact with the greatest number of total reproductive nodes per plant than the other concentrations. UM 2-4 also showed the highest number of total pod at 75 ppm concentration. The 50 ppm concentration is recommended to be given since it can influence the number of filled pod, number of total pods, seed thickness and number of total reproductive nodes per plant. The gibberellin concentration significantly influenced the number of filled pods, number of total pods, and number of total reproductive nodes per plant.